Design and investigation of dual-axis electrostatic driving MEMS scanning micromirror - Longqin Wu; Yu-Sheng Lin (International Journal of Optomechatronics)
Micro-electro-mechanical system (MEMS) is once proposed in 1970s and evolving rapidly. Current researchers are seeking for better designs and better applications for MEMS actuators. This work presents an electrostatic driven dual-axis scanning micromirror, i.e., two-dimensional (2D) scanning micromirror with mirror size of 500 μm × 500 μm. The scanning mirror is implemented by using bulk micromachining process on silicon on insulator (SOI) substrate, which is compatible with present complementary metal oxide semiconductor (CMOS) manufacturing technology. The scanning frequency of the slow axis and the fast axis is 4.87 kHz and 31.15 kHz, respectively. The impact factors of the dimensions of comb fingers and torsion beams are analyzed and discussed in this study. Under the driving voltage difference of 100 volts and 70 volts, the deviation angle is 4.57° × 13.08°. Therefore, a simple design of a dual-axis MEMS scanning micromirror is proposed, which can be precisely controlled without additional complex sensors or circuits.